Al-Mustadrak: A Hadith Compilation Both Praised and Criticized - Jafar Shodiq; Alfath; Rizzaldy Satria Wiwaha; Engkos Kosasih; Irwan Abdurrahman (al-Afkar, Journal For Islamic Studies, 2026)
Thi s study aims to examine comprehensively Kitāb al-Mustadrak ʿalā al-Ṣaḥīḥayn by al-Ḥākim al-Naysābūrī (d. 405 H), one of the most significant works in the hadith corpus, composed with the purpose of completing authentic traditions that were not included in Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim. The research seeks to explore the background of the book’s compilation, the author’s scholarly profile, al-Ḥākim’s methodology in collecting and evaluating hadiths, as well as the responses of later scholars concerning the authenticity and quality of the narrations contained within. This study employs a qualitative method using a descriptive-analytical approach through a library-based examination of primary and secondary sources, including al-Mustadrak, Talkhīṣ al-Mustadrak by al-Dhahabī, and critical commentaries from both classical and contemporary hadith scholars. The findings indicate that although al-Ḥākim claimed that all hadiths in al-Mustadrak meet the authenticity criteria applied by al-Bukhārī and Muslim, many narrations within the collection have been criticized for their weak chains of transmission and problematic textual content. Nevertheless, the book holds substantial value in hadith studies, particularly as a comparative reference and a critical resource within the classical and modern scholarly traditions. Thus, al-Mustadrak remains an essential work for understanding the dynamics of hadith authenticity, transmission, and criticism throughout Islamic intellectual history.